Aktualisasi Humanisme Religius Menuju Humanisme Spiritual dalam Bingkai Filsafat Agama - Husna Amin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
An understanding of the universal values of human existence that does not  differ individually, an attitude humanistic into the spirit of the movement of  religious and philosophical. Humanism was born in the spectrum of modern  thought, just fight for these values. But in its development, teaching the  humanities have negative implications in addition to providing positive things for  the spirit of humanity. Behind these two spheres, it must be admitted that neither  philosophy nor religion, basically moving and growing in a single purpose, which  is to fight for and defend human life order. Both will not be meaningful, if it does  not consider the value of humanity. Religious Humanism is a philosophical  connectivity that determines the course of human life taken is objective, rational,  ethical and religious. Human freedom is a central theme religious humanism, but  the freedom he fought for freedom not absolute or medieval antithesis which  incidentally is considered balanced between religious interests and the interests of  humanity. Man is the center of reality, so everything must be returned to him and  the phenomenon of human existence is not justified interpretation of the  phenomenon that place people as marginal entities